Pastoral conflicts and (dis)trust: Evidence from Nigeria using an instrumental variable approach - Daniel Tuki (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Although the incidence of conflicts between Fulani nomadic pastoralists and sedentary farmers in Nigeria have risen significantly during the last decade, no study has, to the best of my knowledge, examined how these conflicts influence distrust of members of the Fulani ethnic group and the larger Muslim population, nor the conditions under which these conflicts, which are primarily about competition over land and water resources, morph into religious conflicts. Using novel survey data collected from Kaduna, the state with the third highest incidence of pastoral conflicts in Nigeria, this study fills these gaps. The regression results show that exposure to pastoral conflicts cause distrust of members of the Fulani ethnic group and Muslims; although the size of the effect is much larger for the Fulani compared to Muslims. This shows that the population in Kaduna tend to conflate the Fulani with Muslims. Religious polarization was found to catalyze the process of resource conflicts turning religious. – – Obwohl die Häufigkeit von Konflikten zwischen nomadischen FulaniPastoralisten und sesshaften Bauern in Nigeria in den letzten zehn Jahren erheblich zugenommen hat, wurde meines Wissens in keiner Studie untersucht, wie diese Konflikte das Misstrauen zwischen Mitgliedern der Fulani-Ethnie und der muslimischen Bevölkerung insgesamt beeinflussen und unter welchen Bedingungen diese Konflikte, bei denen es in erster Linie um den Wettbewerb um Land- und Wasserressourcen geht, in religiöse Konflikte umschlagen. Die vorliegende Studie füllt diese Lücken mit Hilfe von neu erhobenen Umfragedaten aus Kaduna, dem Bundesstaat mit der dritthöchsten Anzahl an pastoralen Konflikten in Nigeria. Die Ergebnisse der Regressionsanalyse zeigen, dass das Auftreten von Hirtenkonflikten Misstrauen gegenüber Mitgliedern der Fulani-Ethnie und Muslimen hervorruft; allerdings ist der Effekt bei den Fulani wesentlich größer als bei den Muslimen. Dies zeigt, dass die Bevölkerung in Kaduna dazu neigt, die Fulani mit Muslimen zu verwechseln. Außerdem wurde festgestellt, dass die religiöse Polarisierung den Prozess der religiös werdenden Ressourcenkonflikte katalysiert.
Keywords: D74; O13; Q34; 300; Pastoral conflict; Farmer-herder conflict; trust; Fulani; Religion; KadunaState; Nigeria